The influence of environmental factors on the population genetic structure of the pedunculate oak (Quercus robur L.) in Belarus - Padutov, Vladimir E. (Journal of the Belarusian State University. Ecology, 2022)
Pedunculate oak (Quercus robur L.) is one of the main forest forming species in the Republic of Belarus. 18 allelic variants were identified by means of microsatellite loci analysis, which are grouped into 17 different combinations (haplotypes). Twelve of them are rare (the total frequency of occurrence is 15 %) and five are widespread (the proportion of occurrence varies from 7 to 48 %). The last of the named groups includes haplotypes No. 1 (gdt189, gdt3123, gdt4142, gcd494, gcd574, gkk4109), No. 2 (gdt190, gdt3120, gdt4141, gcd495, gcd574, gkk4109), No. 3 (gdt189, gdt3120, gdt4141, gcd494, gcd575, gkk4109), No. 8 (gdt189, gdt3121, gdt4142, gcd494, gcd574, gkk4109). It was found that the geographical distribution of the dominant haplotypes from west to east (along the gradient of climate continentality increasing) has the following order No. 8 - No. 7 - No. 3 - No. 1 - No. 2. It was revealed that haplotype No. 3 is predominantly found in oak forests growing on hills. Haplotype No. 8 prones to form forest stands in depressions, while haplotypes No. 1, No. 2 and No. 7 mainly occupied middle relief elements. The actually observed and theoretically expected frequencies of occurrence in different types of oak forests are close to each other only in the case of haplotype No. 2. For haplotypes No. 1 and No. 8 opposite tendencies of distribution were revealed. In those forest types where for haplotype No. 1 there was an increase in the actual frequency of occurrence compared to the expected one, for haplotype No. 8 there was opposite situation. The reverse trend was also true for this pare of haplotypes. The second pair for which opposite tendencies of distribution were also revealed is haplotypes No. 3 and No. 7.